Enantioselective preparation of mechanically planar chiral rotaxanes by kinetic resolution strategy - Ayumi Imayoshi (Nature Portfolio, 2021)
Since the discovery of mechanically planar chiral rotaxanes and topologically chiral catenanes, their asymmetric synthesis has been a long-standing challenge. Here, the authors report enantioselective preparation of mechanically planar chiral rotaxanes with up to 99.9% ee in 29% yield.